INOVASI RUMAH VERTIKAL KEPITING BAKAU (RVKB) BAGI KELOMPOK BUDIDAYA NELAYAN KAMPUNG LETTE, MAKASSAR - Hamrun, Hamrun; Amalia, Andi Annisa; Wahyu, Farhanah (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service program themed "Vertical Mangrove Crab House Innovation" aims to enhance the economic and social independence of the Fishermen's Cultivation Group in Kampung Lette, Makassar. This program emphasizes the principles of the blue economy, focusing on the sustainable management of coastal resources. The approach involves socialization, training, and mentoring the community in the application of mangrove crab cultivation technology based on vertical apartment systems and water recirculation. Active participation from the fishermen's group and the local community enables them to contribute actively at each stage of the process. This activity resulted in a significant increase in community knowledge and skills related to crab cultivation technology, as well as improvements in productivity and the quality of cultivated crabs. Additionally, the program successfully raised community awareness about the importance of preserving mangrove ecosystems as the natural habitat of mangrove crabs. The implementation of this model provides economic benefits to the community, contributes to the preservation of the coastal environment, and can be replicated in other coastal communities to expand its positive impact.Kegiatan pengabdian bertema inovasi Rumah Vertikal Kepiting Bakau bertujuan untuk meningkatkan kemandirian ekonomi dan sosial Kelompok Budidaya Nelayan di Kampung Lette, Makassar. Program ini mengedepankan prinsip-prinsip blue economy, dengan fokus pada pengelolaan sumber daya pesisir yang berkelanjutan. Pendekatan yang digunakan melibatkan sosialisasi, pelatihan, dan pendampingan masyarakat dalam penerapan tekonologi budidaya kepiting bakau berbasis sistem apartemen vertikal dan resirkulasi air. Partisipasi aktif kelompok nelayan dan masyarakat setempat, memungkinkan mereka berkontribusi aktif dalam setiap tahapan kegiatan. Kegiatan ini menghasilkan peningkatan signifikan dalam pengetahuan dan keterampilan masyarakat terkait teknologi budidaya kepiting, serta peningkatan produktivitas dan kualitas hasil budidaya. Selain itu, kegiatan ini juga berhasil meningkatkan kesadaran masyarakat tentang pelestarian ekosistem mangrove sebagai habitat alami kepiting bakau. Penerapan model ini memberikan manfaat ekonomi bagi masyarakat. Selain itu, berkontribusi pada pelestarian lingkungan pesisir dan dapat direplikasi di komunitas pesisir lainnya untuk memperluas dampak positifnya.